2016
DOI: 10.1159/000452722
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Thyroid Function after Presenting with Hashimoto Thyroiditis Is Different between Initially Euthyroid Girls with and Those without Turner Syndrome

Abstract: Aim: To prospectively investigate, during a 5-year follow-up, whether the prognosis of thyroid function with Hashimoto thyroiditis (HT) is different in euthyroid girls with Turner syndrome (TS) than in euthyroid girls without TS. Design: In 66 TS girls and 132 non-TS girls with euthyroid HT and similar thyroid functional test results at HT diagnosis, we followed up the evolution of thyroid status over time. Results: At the end of follow-up, the TS girls exhibited higher TSH levels, lower fT4 levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
11
1
1
Order By: Relevance
“…All the studied patients with TA were asymptomatic and no one fulfilled the criteria of overt hypothyroidism. Although the presence of thyroid-specific autoantibodies was the only manifestation of thyroid dysfunction in half of our patients with TA, they may develop an overt disease in the future, as presented in previous studies (2123). By comparing the phenotypic aspects of HD in TS patients and non-TS population, Aversa et al showed that the biochemical features of thyroid functions are less severe in TS-patients; this may be caused by a less aggressive autoimmune process as well as the increased vigilance of the physicians taking care of TS-patients, thus leading to earlier diagnosis (24).…”
Section: Discussionsupporting
confidence: 52%
“…All the studied patients with TA were asymptomatic and no one fulfilled the criteria of overt hypothyroidism. Although the presence of thyroid-specific autoantibodies was the only manifestation of thyroid dysfunction in half of our patients with TA, they may develop an overt disease in the future, as presented in previous studies (2123). By comparing the phenotypic aspects of HD in TS patients and non-TS population, Aversa et al showed that the biochemical features of thyroid functions are less severe in TS-patients; this may be caused by a less aggressive autoimmune process as well as the increased vigilance of the physicians taking care of TS-patients, thus leading to earlier diagnosis (24).…”
Section: Discussionsupporting
confidence: 52%
“…Turner syndrome (TS) is another common chromosomopathy, that has been reported to be associated with an increased risk of various ADs, but especially HT and CD (40, 41). The link with TS has been shown to have negative repercussions on the evolution over time of thyroid function in girls with TS (37, 38, 42, 43), which suggested the opportunity of a strict monitoring of thyroid tests in these patients, in order to recognize at a proper time a possible deterioration from euthyroidism to hypo- or hyperthyroidism (42, 43). The association with TS, however, seems that it is not able to modify the clustering of NTADs in the girls with HT (42).…”
Section: Discussionmentioning
confidence: 99%
“…ATDs had been reported to be more frequent in girls with TS than in the general population [ 6 , 10 , 11 ], covering a spectrum of phenotypes. They include Hashimoto’s thyroiditis (HT)—which is considered the most common autoimmune thyroid disease, and Graves’ disease (GD)—which causes hyperthyroidism [ 7 , 12 16 ].…”
Section: Introductionmentioning
confidence: 99%